Design of Mechanical Coconut Dryer Desiccated Coconut - Karten Malau; Lukman Adlin Harahap; Achwil Putra Munir (Universitas Sumatera Utara, 2015)
Coconut is one of multifunction plant, every part of it was useful. One of its usage is fruit flesh grating and then dried to avoid bacteria’s growth, so it can be used to prepare bread, biscuit, candy, taking the coconut milk and ingredient of coconut flour. Therefore, the writer was design and constructed grated coconut dryer. This research has been done since April to August 2014 in Laboratorium Keteknikan Pertanian, Fakultas Pertanian Universitas Sumatera Utara, Medan by literature study, construction testing and observing the equipment. The parameters observed were effective capacity, tested of the equipment, analyzed the economic value. Based on this research it was summarized that the effective capacity of the equipment was 0,67 kg/hr, basic costs were Rp.15.391,36 for the first year, Rp. 13.739,39 for the second year, Rp. 13.189,49 for the third year, Rp. 12.915,02 for the fourth year and Rp. 12.750,65 for the fifth year, break event point was 752,21 kg/year for the first year, 405 kg/year for the second year, 290 kg/year for the third year, 232,52 kg/year for the fourth year and 198,03 kg/year for the fifth year, net present value was Rp. 118,963.293,2, internal rate of return was 43,56%, its mean that this equipment was worthy to use. Key words: coconut dryer, coconut flesh, dry grated coconut